Risk Assessment in Audit - N. I. Dorosh (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The article's objective is to demonstrate the causality of risks involved in the audit, in order to minimize the audit risk associated with formulating the adequate audit conclusion based on the risks of the company's financial reporting and the effectiveness of company's internal control.The meaning of entrepreneurial risk and risk management methods at company level are discussed, with emphasizing the impact of risks on the reliability of financial reporting. Four components of the risk involved in external audit are outlined and discussed: entrepreneurial risk, risk of financial reporting, risk of taking obligations, risk of audit. The causality between risk components having impact on audit is illustrated. The essence and methods of risk management in audit are analyzed. It is demonstrated that the issue of whether or not a client be accepted for audit service and whether or not the audit-based cooperation with it be prolonged constitutes a primary decision with respect to each audit. Factors behind the auditor's decision to accept a new client or continue to work with the previous one are highlighted. It is emphasized that the honesty of management personnel has the foremost importance for an auditor; sources of information about the honesty of management personnel are shown.